‘Shock and Awe’: A critique of the Ghana-centric child trafficking discourse - Okyere, Samuel (Anti-Trafficking Review, 2017)
This paper is a critique of the dominant anti-trafficking discourse and activism in Ghana. It argues that the discourse grossly underplays the role of external forces in shaping the conditions underpinning children’s labour mobility in the past and the hardships underpinning the phenomenon today. In place of critical analysis and understanding, anti-child-trafficking campaigns employ melodramatic ‘shock and awe’ tactics and a tendency to blame local culture or traditions for activists’ claims of ‘pervasive’ child trafficking in the country. The paper suggests that dominant anti-trafficking discourse and activism in Ghana thus reinvigorate historic and persistent external causal agents of inequality which drive Ghanaian children’s labour mobility today. The paper demonstrates this problem and offers correctives to it.